Implikasi Exchange Rate, Tunneling Incentive, dan Mekanisme Bonus Terhadap Keputusan Transfer Pricing - Hanung Deswinta Syaharani; Nera Marinda Machdar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Today's global economic growth is driven by globalization, which facilitates cross-border transactions, investment, and international trade. However, globalization also allows companies to reduce their tax burden through transfer pricing practices. This study aims to examine in depth the factors that influence the magnitude of transfer pricing. Transfer pricing often occurs in companies with high profit goals and tax avoidance. Concentrated ownership structures allow management to divert wealth for personal interests or majority shareholders. The method used is a descriptive approach using literature studies which are taken from journals and articles relevant to the research topic.